Molecular Design of Antifouling Polymer Brushes Using Sequence-Specific Peptoids - Lau, King Hang Aaron (Adv Mater Interfaces, 2015)
Material systems that can be used to flexibly and precisely define the chemical nature and molecular arrangement of a surface would be invaluable for the control of complex biointerfacial interactions. For example, progress in antifouling polymer biointerfaces that prevents nonspecific protein adsorption and cell attachment, which can significantly improve the performance of an array of biomedical and industrial applications, is hampered by a lack of chemical models to identify the molecular features conferring their properties. Poly(N-substituted glycine) “peptoids” are peptidomimetic polymers that can be conveniently synthesized with specific monomer sequences and chain lengths, and are presented as a versatile platform for investigating the molecular design of antifouling polymer brushes. Zwitterionic antifouling polymer brushes have captured significant recent attention, and a targeted library of zwitterionic peptoid brushes with different charge densities, hydration, separations between charged groups, chain lengths, and grafted chain densities, is quantitatively evaluated for their antifouling properties through a range of protein adsorption and cell attachment assays. Specific zwitterionic brush designs are found to give rise to distinct but subtle differences in properties. The results also point to the dominant roles of the grafted chain density and chain length in determining the performance of antifouling polymer brushes.